London dispersion forces and steric effects within nanocomposites tune interaction energies and chain conformation - Baode Zhang; Snežana D. Zarić; Sonja S. Zrilić; Iosif Gofman; Barbara Heck; Günter Reiter (Communications Chemistry)
Abstract The interplay between attractive London dispersion forces and steric effects due to repulsive forces resulting from the Pauli principle often determines the geometry and stability of nanostructures. Aromatic polyimides (PI) and carbon nanotubes (CNT) were chosen as building blocks as two components in the hetero delocalized electron nanostructures. Two PIs, having the same diamine part and different linkage substituents between two phenyl rings of dianhydride part, one linked with ether bond (C-O-C) (OPI), the other with C-(CF3)2 (FPI), were investigated. Surprisingly, two CNT/PI nanocomposites show distinct failure mode from CNT yielding to CNT pull-out failure. Calculation of the interaction energy and chain conformations of each PI upon CNT was performed by accurate density functional theory (DFT) calculations and molecular dynamic simulation (MDS). OPI chain adopt helically wrapping conformation around CNT with relatively strong interaction energy. FPI chain take the one-side wavelike conformation upon CNT with relatively weak interaction energy.